The Development of check-points on the border of Kazakhstanand People’s Republic of China in Xinjiang. (Journal of Oriental Studies, 2016)
In this article we discuss the Development of check-points on the border of Kazakhstanand People's Republic of China in Xinjiang.
Keywords: Custom; customs duties; customs protection